Community Empowerment Through Biomass Wass Management: A Case Study of Kang Ebit Programme - Sukmayadevi, Sukmayadevi; Kinara, Lingga Gayuh; Trianto, Hasfin Bagus; Irawati, Shinta Tris (Edujavare Publishing, 2025)
The increasing volume of seasonal biomass waste such as siwalan (lontar palm) peels and coconut shells in Kapu Village, Merakurak Sub-district, Tuban Regency, has led to significant environmental and social challenges. This waste is often underutilized and typically burned in the open, causing air pollution and contributing to carbon emissions estimated at ±6–8 tons of CO₂ per year. Meanwhile, the majority of the village’s working-age population depends on seasonal agriculture, with limited alternative economic opportunities especially for vulnerable groups such as the elderly, housewives, persons with disabilities, and the unemployed. This community engagement program introduced briquette production from siwalan peels and coconut shells through a participatory approach, simple technology transfer, and entrepreneurship mentoring. The initiative resulted in increased community skills in briquette production and the emergence of local entrepreneurial efforts. Furthermore, it helped reduce open burning practices and created new income sources for vulnerable groups. The program demonstrates that biomass waste utilization can not only benefit the environment but also promote inclusive economic empowerment in rural communities.